Westerns. High Plains Drifter ; Destry rides again ; Winchester '73 / [videorecording (DVD)] - Brand, Max, 1892-1944; Lake, Stuart N. (Universal Studios Home Entertainment, 2012)
In High Plains Drifter a mysterious stranger rides out of the desert and into the town of Lago whose citizens hire him to protect them from three gunmen. In Destry rides again Destry, a mild-mannered deputy who doesn't like guns ... is called to restore order to the hopelessly corrupt frontier town of Bottleneck. Though reluctant to undertake such an enormous task, he's soon roped into action after meeting the seductive Frenchy, an alluring saloon girl who belts out unforgettable show-stoppers like "The Boys in the Back Room," while winning the hero's heart. In Winchester '73 An engaging frontiersman attempts to track down his father's murderer and the whereabouts of his one-of-a-kind rifle, the Winchester '73, as it passes among a rogue's gallery of owners including a crazed highwayman, an immoral gunrunner, a young Indian chief, and Stewart's own murderous brother.